2000
DOI: 10.2355/isijinternational.40.58
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Sheet Thickness on Shear Deformation in Ferritic Rolling of IF-Steel Sheets.

Abstract: The effect of sheet thickness on shear deformation and texture for the ferrite rolling has been studied.The shear deformation was estimated from the distorted shape of inserted wire before rolling and FEM simulation. The deformed shape of inserted wires and FEM results showed that the shear strain decreased with increasing initial sheet thickness. The measuredand simulated textures also showed that the Goss component changedto Dillamore componentas the thickness increased, From rolling simulation of 20'1-reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…In the present study, the interface friction is dominant, where the parameter l/d is sufficiently large. 16,17) Since the mill with 310 mm in roll diameter was used in not only two-layer stack ARB but also six-layer stack ARB, the parameter l/d (7.6 from the first to the third pass in each cycle) of the six-layer stack ARB is smaller than that (9.3) of the two-layer stack ARB, and therefore the two-layer stack ARB introduces higher shear strain.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the interface friction is dominant, where the parameter l/d is sufficiently large. 16,17) Since the mill with 310 mm in roll diameter was used in not only two-layer stack ARB but also six-layer stack ARB, the parameter l/d (7.6 from the first to the third pass in each cycle) of the six-layer stack ARB is smaller than that (9.3) of the two-layer stack ARB, and therefore the two-layer stack ARB introduces higher shear strain.…”
Section: Discussionmentioning
confidence: 99%
“…Here, Ls indicated 0.15 with lubricant and 1.5 without it. Since the effect of temperature in the rolled Al or IF steel sheet on the relation among  eq , , and Ls is small in comparison with the friction effect (Um et al, 2000;Inoue & Tsuji, 2009), it is likely from Figs. 6(a,c) and 11 (b,c) that the strain at the surface is 0.59 and  eq 0.97 for rolling with lubricant and 7.66 and  eq 5.34 for rolling without it.…”
Section: Strain Distributions In Arbmentioning
confidence: 99%
“…The flection of the pin in the embedded-pin method makes the presence of the shear deformation clear. The pin flection in pure aluminum (Lee et al, 2002), interstitial free (IF) steel (Matsuoka et al, 1997;Sakai et al, 1988;Um et al, 2000;Kamikawa et al, 2007), and Type 304 stainless steel (Zhang et al, 1996; sheets rolled at various temperatures has been observed using this method. In the present study, the condition of a commercial 1100 Al sheet rolled at ambient temperature without lubricant and without front and back tensions reported by Lee et al, 2002 Table 1.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 2 more Smart Citations